Análise do Fluxo de Co2 sobre uma Cultura de Soja - -, Zimermann; R., Carneiro H.; V., Moraes J.; L., Escobar O. L.; F., Chavez L.; F., Fiorin L.; J., Amado; C., T. J. (Ciência e Natura, 2007)
Análise do fluxo de CO2 sobre uma cultura de soja